Development of motor control using graphical user interface - Aris, Khairul Anuar (2007)
DC Motor control is very common in robotic application. The developments of this kind of project are widely used in most electronic devices nowadays. There are many application that have been developed based on motor control in electronic field such as in automation, Flexible Manufacturing System (FMS) and Computer Integrated Manufacturing (CIM). The purpose of this project is to develop the Graphical User Interface of Motor Control through MATLAB GUIDE, interface the MATLAB GUI with hardware via communication port and control the DC motor through MATLAB GUI. By using MATLAB GUIDE, it provides a set of tools which simplify the process of laying out and programming GUIs and interface with PIC via serial communication port to control the DC motor. The PIC is used to control motor. As a result, the DC motor is able to be controlled through MATLAB GUI and interface the MATLAB GUI with PIC via serial communication port.